A high-value-added application of the stems of Rheum palmatum L. as a healthy food: the nutritional value, chemical composition, and anti-inflammatory and antioxidant activities. Issue 9 (7th April 2022) - Shang, Xiaofei; Dai, Lixia; He, Jian; Yang, Xiaorong; Wang, Yu; Li, Bing; Zhang, Jiyu; Pan, Hu; Gulnaz, Ilgekbayeva
Abstract : SRP is shown to have nutritional value, exhibit anti-inflammatory and antioxidant activities, and have the potential to be utilized as a sustainable resource in the food and pharmaceutical industries. Abstract : Rhubarb has edible stems or stalks. In this paper, we investigated the nutritional value, chemical composition, and bioactivities of Rheum palmatum stems (SRP) and analyzed the mode of action. SRP exhibited biosafety and had nutritional value, with abundant essential amino acids and minerals. Based on network pharmacology and western blot tests, we found that it showed anti-inflammatory activity via the PI3K-Akt-mediated NF-κB pathway. Out of 20 compounds identified using UPLC-ESI-Q-TOF/MS analysis, cirsiliol and hydrangenol were active compounds and they inhibited NO production in RAW264.7 cells induced by LPS. The alleviation of an inflammatory response is combined with a decrease in oxidative stress, and SRP showed antioxidant activity via attenuating antioxidant enzymes, scavenging free radicals, improving the mitochondrial membrane potential, and decreasing the reactive oxygen species level. These results indicated that SRP, with abundant flavonoids and a good nutritional composition, could be used as a dietary supplement for food applications.